FERTILIZER APPLICATION TECHNOLOGIES IN MODERN GREENHOUSE FARMS - BABYN, IHOR; LUTS, PAVLO; RIPA, SERHIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
In the article, a comprehensive analysis of modern technologies of fertilizer application of greenhouse farms is carried out, in particular, the importance of fertigation as one of the leading methods of integrated supply of fertilizers and water through drip irrigation systems is emphasized. This method is effective due to precise control over the amount of nutrients supplied to the plants. In particular, the article examines different types of fertigation equipment: proportional metering pumps, Wintour injectors and special fertilizer mixers. These devices not only guarantee the exact dosing of nutrients, but also reduce the consumption of fertilizers, which has a positive effect on increasing yields.The importance of automating the fertilizer application process, which minimizes the impact of the human factor, reduces the risk of errors, and ensures constant monitoring of the concentration of nutrients, is emphasized separately. This allows you to maintain stable conditions for the growth of crops. The introduction of precision farming systems, which adapt the application of fertilizers to the individual needs of each zone of the greenhouse, contributes to the rational use of resources and the reduction of environmental burden.Hydroponic systems are also analyzed as one of the modern approaches to growing crops in greenhouses. They allow you to fully control the process of plant nutrition, excluding dependence on soil conditions, which makes this method especially effective in greenhouses. The article emphasizes that the use of hydroponics and other advanced technologies helps to optimize the use of resources and increase the productivity of agricultural production.At the end of the article, the prospects for the further development of fertigation technologies, automation of processes and the introduction of innovative approaches in greenhouse farms aimed at increasing efficiency, productivity and reducing the negative impact on the environment are highlighted.
Keywords: fertigation; mixing; fertilizer application; fertilizer mixer; proportional dosing pump; dosing accuracy; greenhouse farming; hydroponics